Forest management as an element of environment development = Gospodarka leśna jako element kształtowania środowiska - Jaszczak, Roman; Gołojuch, Piotr; Wajchman-Świtalska, Sandra; Miotke, Mariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The implementation of goals of modern forestry requires a simultaneous consideration of sustainable development of forests, protection, needs of the environment development, as well as maintaining a balance between functions of forests. In the current multifunctional forest model, rational forest management assumes all of its tasks as equally important. Moreover, its effects are important factors in the nature and environment protection.
Keywords: forest management; sustainable forest management; afforestation; cutting methods; regeneration; urban forest; gospodarka leśna; zrównoważona gospodarka leśna; zalesianie; rębnie; odnowienia; lasy miejskie